Rethinking naive realism. - Beck, Ori (Philosophical Studies, 2019)
Perceptions are externally-directed—they present us with a mind-independent reality, and thus contribute to our abilities to think about this reality, and to know what is objectively the case. But perceptions are also internally-dependent—their phenomenologies depend on the neuro-computational properties of the subject. A good theory of perception must account for both these facts. But naive realism has been criticized for failing to accommodate internal-dependence. This paper evaluates and responds to this criticism. It first argues that a certain version of naive realism, often called "selectionism", does indeed struggle with internal-dependence. It then develops an alternate version of naive realism which does not. This alternate version, inspired by an idea of Martin's, accommodates the internal-dependence of perceptions by recognizing the role that the subject's neuro-computational properties play in shaping perceptual phenomenology. At the same time, it retains the distinctive naive realist account of the external-directedness of perceptions.